2007
DOI: 10.1111/j.1365-313x.2007.03118.x
|View full text |Cite|
|
Sign up to set email alerts
|

Seed dormancy release in Arabidopsis Cvi by dry after‐ripening, low temperature, nitrate and light shows common quantitative patterns of gene expression directed by environmentally specific sensing

Abstract: SummaryThe depth of seed dormancy can be influenced by a number of different environmental signals, but whether a common mechanism underlies this apparently similar response has yet to be investigated. Full-genome microarrays were used for a global transcript analysis of Arabidopsis thaliana Cape Verde Island accession seeds exposed to dry after-ripening (AR), or low temperature, nitrate and light when imbibed. Germination studies showed that the sensitivity of imbibed seeds to low temperature, nitrate and lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
267
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(297 citation statements)
references
References 63 publications
(185 reference statements)
21
267
0
9
Order By: Relevance
“…In the dormant low-temperature-set seeds, cell wall modification, heat shock, and protein degradation were the most prominent categories, whereas in the low dormant seeds, translation, photosynthesis, seed storage proteins, and ethylene were better represented. Broadly speaking, this result is in line with previous studies that have compared seed dormancy states (Finch-Savage et al, 2007), which also identified increased gene expression associated with translation and photosynthesis as indicative of low dormant states. We confirmed the differential expression in dry seeds set at 10 or 208C by real-time PCR using independent samples ( Figure 1E).…”
Section: Identification Of Temperature-dependent Transcripts In Matursupporting
confidence: 91%
See 1 more Smart Citation
“…In the dormant low-temperature-set seeds, cell wall modification, heat shock, and protein degradation were the most prominent categories, whereas in the low dormant seeds, translation, photosynthesis, seed storage proteins, and ethylene were better represented. Broadly speaking, this result is in line with previous studies that have compared seed dormancy states (Finch-Savage et al, 2007), which also identified increased gene expression associated with translation and photosynthesis as indicative of low dormant states. We confirmed the differential expression in dry seeds set at 10 or 208C by real-time PCR using independent samples ( Figure 1E).…”
Section: Identification Of Temperature-dependent Transcripts In Matursupporting
confidence: 91%
“…In nature, primary dormant seeds must remain ungerminated in darkness to enter the soil seed bank, where low temperature drives the transition of imbibed seeds into secondary dormancy (Finch-Savage et al, 2007). To test this, we performed experiments testing the ability of seeds matured at three temperatures to resist germination in the dark during extended chilling ( Figure 1G).…”
Section: Identification Of Temperature-dependent Transcripts In Maturmentioning
confidence: 99%
“…Nitrate as a spatial signal Nitrate has long been known as one of the key variables in the loss of seed dormancy and promotion of germination (Baskin and Baskin, 1998;Alboresi et al, 2005;Finch-Savage et al, 2007;Matakiadis et al, 2009). Seeds use nitrate sensing as a gap detection mechanism, as nitrate levels inform about the presence of competing plants that deplete soil nitrate (Pons, 1989).…”
Section: Z Huang Et Al 160mentioning
confidence: 99%
“…In wild‐type plants, GPT2 expression is induced in imbibed seeds (Finch‐Savage et al . 2007), in response to exogenous and endogenous increases in sucrose (Lloyd & Zakhleniuk 2004; Gonzali et al . 2006), in response to an increase in light intensity (Athanasiou et al .…”
Section: Introductionmentioning
confidence: 99%